HUBUNGAN KONSUMSI DAUN KELOR DENGAN PEMBERIAN ASI EKSKLUSIF PADA IBU MENYUSUI SUKU TIMOR DI KELURAHAN KOLHUA KECAMATAN MAULAFA KUPANG - Roslin E. M. Sormin (CHMK NURSING SCIENTIFIC JOURNAL, 2018)
ASI (Breast milk) is one of the best food sources for newborns because it has so many important substances to increase immunity to prevent disease. This nutritional factor needs to be considered by a mother in the breastfeeding process to increase breast milk production in addition to other factors such as breast care and baby suction that stimulates prolactin hormone for breast milk production. Moringa (Moringa oleifera) is one of the Timorese food ingredients. Moringa leaves contain phytosterol which can increase milk production for breastfeeding women and overcome anemia in children and pregnant women because it contains many important nutrients such as vitamin A, vitamin C, calcium, iron and protein. This study found that in Timorese mothers in Kolhua Subdistrict, Maulafa Kupang City, there was a habit of consuming food in the form of nuts and leaves such as katuk leaves and kelor leaves to increase the production of breast milk. Moringa leaves have been known by 90% of respondents of Timorese mothers in Kolhua Subdistrict, Maulafa Kupang City, to increase milk production. All respondents (100%) had the habit of consuming Moringa as a vegetable with different frequencies. There is a relationship between the frequency of consumption of Moringa leaves and exclusive breastfeeding for Timorese mothers in Kolhua Subdistrict, Maulafa Kupang City.